Bottom-up synthesis of liquid-phase-processable graphene nanoribbons with near-infrared absorption - Narita, Akimitsu; Verzhbitskiy, Ivan A.; Frederickx, Wout; Mali, Kunal S.; Jensen, Soeren Alkaersig; Hansen, Michael Ryan; Bonn, Mischa; De Feyter, Steven; Casiraghi, Cinzia; Feng, Xinliang; Muellen, Klaus (ACS nano, 2014)
Structurally defined, long (>100 nm), and low-band-gap (∼1.2 eV) graphene nanoribbons (GNRs) were synthesized through a bottom-up approach, enabling GNRs with a broad absorption spanning into the near-infrared (NIR) region. The chemical identity of GNRs was validated by IR, Raman, solid-state NMR, and UV-vis-IR absorption spectroscopy. Atomic force microscopy revealed well-ordered self-assembled monolayers of uniform GNRs on a graphite surface upon deposition from the liquid phase. The broad absorption of the low-band-gap GNRs enables their detailed characterization by Raman and time-resolved terahertz photoconductivity spectroscopy with excitation at multiple wavelengths, including the NIR region, which provides further insights into the fundamental physical properties of such graphene nanostructures. (Chemical Equation Presented).
CRIS-Team Scopus Importer:2023-03-20
Keywords: Band-gap engineering; Cyclodehydrogenation; Diels-Alder reaction; Graphene nanoribbon; Near-infrared absorption